WATERBIRD MIGRATION IN TAUDAHA LAKE, KATHMANDU, NEPAL: UNDERSTANDING FACTORS DRIVING MIGRATION AT A SMALL STOPOVER SITE - K. B. Khatri; H. B. Katuwal; S. Sharma; H. P. Sharma (Journal of Animal and Plant Sciences, 2023)
Anthropogenic activities in the wetland and surrounding land are threatening the waterbirds. Population dynamics and waterbirds’ arrival and departure dates are also influenced by wetland characteristics, food availability, and weather conditions. However, this information is rarely available for Taudaha Lake, a small stopover site in the Kathmandu Valley, Nepal, for many north-south migratory waterbirds. We observed the waterbird species, counted their number, and recorded their exact arrival date (October 2019) and departure date from January 2019 to April 2020. In addition, we recorded the air temperature and humidity of the lake during the monitoring time to identify the potential effects of these weathers on the arrival departure of migratory waterbirds. We developed a linear model to understand the factors influencing the arrival and departure of migratory waterbirds. Altogether we recorded ten migratory waterbird species, including one globally threatened species that used Taudaha as a stopover site during their migration. Arrival and departure times vary among the species. With increasing temperature, the migratory bird population decreases at the lake. Despite smaller area, Taudaha Lake at Kathmandu Valley acts as an important stopover site to facilitate the north-south migration of waterbirds. Therefore, we recommend local government to avoid concrete constructions on the lake.
Keywords: Arrival and departure time; Bird migration; Stopover site; Temperature; Waterbirds